Increased Interleukin-17F is Associated with Elevated Autoantibody Levels and More Clinically Relevant Than Interleukin-17A in Primary Sjögren’s Syndrome - Yuzhou Gan; Xiaozhen Zhao; Jing He; Xu Liu; Yun Li; Xiaolin Sun; Zhanguo Li (Journal of Immunology Research)
Th17 related immune response is pathogenic in primary Sjögren’s syndrome (pSS). However, the role of IL-17F, one potent inflammatory member of IL-17 family cytokines in pSS, has not been specifically defined. We recruited one hundred and nine pSS patients and forty-two healthy controls and their serum levels of IL-17A and IL-17F were determined by multiplex cytokine assays. White blood cell, red blood cell, neutrophil, lymphocyte, IgM, IgG, C3, C4, RF, ANA, anti-SSA antibody, and anti-SSB antibody were measured by standard laboratory techniques. EULAR Sjögren’s syndrome disease activity index (ESSDAI) score was also evaluated accordingly. We found that IL-17F was significantly increased in pSS patients. Elevated levels of IL-17F were associated with increased IgG and IgM, higher titers of ANA and anti-SSA antibodies, and reduction of C3 and C4. Patients with higher disease activity also showed higher serum IL-17F levels. However, serum IL-17A was only increased in patients with longer disease duration and showed few correlation with clinical and laboratory features in pSS patients. In conclusion, IL-17F was correlated with increased autoantibody levels and disease activity in pSS and is more clinically relevant than IL-17A.